Synthesis of magnetic sorbents modifie with moringa oleifera extracts for the removals of environmental orgamnic pollutants - Kgatitsoe, Maureen Maletsatsi (My University, 2018)
Modern developments on nanoparticles (NPs) has led to new innovation in nanoparticles that can be used for the treatment of polluted water. Magnetic NPs are of great interest because of their unique properties and promising applications. Their stability is essential to prevent them from agglomeration, hence, modification with a specific coating layer can assist in the selectivity function and stability of the magnetic NPs. In this work, a magnetic organic nano-adsorbent was synthesized and investigated for the application in the extraction of nitroaromatic explosive compounds from aqueous solutions. The approach was to find a possible synergy between the adsorptive properties of Moringa oleifera and the high surface area of the NPs. The magnetic NPs were utilized for their ferromagnetic properties which assist in the extraction procedure. M. oleifera was used as a natural coating agent to functionalize the magnetic NPs and also to provide stability. There are numerous chemical procedures to synthesize magnetite and one of the simplest and convenient procedures, co-precipitation, was used in this study. Magnetite can be easily oxidized under ambient conditions, hence, in order to prevent oxidation, M. oleifera extracts were used as a coating agent. The synthesized uncoated magnetite NPs and M. oleifera coated magnetite NPs were characterized by powder X-ray diffraction (PXRD), Fourier transform infrared (FTIR), Brunauer, Emmett and Teller (BET) and thermogravimetric analysis (TGA). The M. oleifera leaf extract was obtained using pressurized hot water extraction (PHWE) at 80°C and the seed extract was purchased as a pure oil. Both the M. oleifera leaf and seed extracts were characterized by FTIR and gas chromatography–mass spectrometry (GC-MS) for possible organic compounds assisting in the stability of the magnetite. From the BET results of the coated magnetic NPs at different times, it was observed that with increasing coating time, the surface area decreased while the pore size increased. To optimize the extraction of nitroaromatic explosive compounds (NAECs), the parameters that were investigated were sample pH, contact time, mass of adsorbent and initial concentration. The optimum value for pH of the sample was found at pH8 and for the contact time an optimum of 120 min was found. The mass of M. oleifera coated magnetic NPs for the maximum removal of explosives were found to be 100 mg. The adsorption capacity of the NAECs was obtained in the range of 0.45 and 0.76 mg g-1 at optimum conditions. During kinetic studies it was observed that the pseudo second order model explained the extent of the adsorption mechanism. It was observed that the Langmuir model was favourable as compared to the Freundlich model. The order of selectivity for the NAECs studied was observed as follows: 2-NT ≈ 3-NT > 4NT > NB > 2,6-DNT > 1,3-DNB. The limit of detection (LOD) found was 0.37 – 4.47 and 0.45 – 5.66 ng.mL-1 for extraction using magnetic NPs coated with M. oleifera leaf and seed extract, respectively. The percentage recovery for the extraction of NAECs at optimum conditions was obtained in the range 14 – 46%.
A Masters dissertation submitted to the Faculty of Science, University of the Witwatersrand in fulfillment of the requirements of the degree of Master of Science, January 2018
Keywords: Metabolites; Extraction (Chemistry); Medical plants